Organic Amendments and Nutrient Leaching in Soil Columns. (1st July 2017) - Adeli, Ardeshir; Read, John; Feng, Gary; McGrew, Rebecca; Jenkins, Johnie
Abstract : Core Ideas: Compost promotes C sequestration in reclaimed coal mine soil. Flue gas desulfurization gypsum reduces P content in leachate. Compost sustains agro‐ecosystem. Substantial amount of applied nutrients can be leached in low organic matter soils. The objective of this study was to determine if the leaching losses of nutrients could be reduced by increasing soil organic matter. In an undisturbed soil column study, fresh and composted broiler litter in the presence or absence of flue gas desulfurization (FGD) gypsum were applied to bermudagrass ( Cynodon dactylon. L.) established on an agricultural soil and a reclaimed coal mine soil in 2014 and 2016, respectively. Columns were leached weekly with 500 mL deionized water, a 100 mL increment. The leachate volume was measured using a graduated cylinder and samples were taken for nutrient analyses. Even though the columns received approximately equivalent N from composted and fresh broiler litter, nitrate N leaching losses were lower with composted than fresh broiler litter (6.61 vs. 9.4 kg ha −1 ). Additionally, leachate from columns treated with composted broiler litter had comparatively less dissolved organic C (5.6 vs.11.7 kg ha −1 ) and P (5.6 vs.6.8 kg ha −1 ), demonstrating that applying composted litter can reduce potential risk of nutrient loss. Addition of FGD gypsum to fresh broiler litter also reduced the P, Cu, and Zn contents in leachate by 67, 73, and 84%, respectively and the reductions were consistent across leaching events. Composted litter application to agricultural soil and reclaimed coal mine soil appears to be a good management practice because it has the potential to promote a more sustainable agro‐ecosystem as compared with NPK fertilizer or fresh broiler litter.